RESPON AYAM PEDAGING YANG DIBERI GULA MERAH DENGAN LEVEL KUNYIT YANG BERBEDA DALAM AIR MINUM - Tabita Naomi Ralahalu; Muhammad Juraid Wattiheluw (Department of Animal Sciences, Faculty of Agriculture, Sriwijaya University, Indonesia, 2022)
This study aims to examine broiler chickens’ response to brown sugar with different levels of turmeric in drinking water. The study was conducted in the Department of Animal Husbandry housing unit, Faculty of Agriculture, Pattimura University, using 90 unsexed Cobb strain broiler chickens aged 1 day, randomized into three treatment groups following a completely randomized design with a 3 x 5 directional pattern. The treatment consisted of P0: feed + drinking water without brown sugar and turmeric, P1: feed + 2% brown sugar and turmeric 10 grams/1 liter of water; P2: feed + 2% brown sugar and turmeric 20 grams/1 liter of water. BRI commercial chicken feed is produced by PT. Japfa Comfeed Indonesia Tbk is used in this study. Feed intake, water intake, body weight gain, and feed conversion were measured variables. The data were analyzed using Anova and continued with the BNT test if there was a significant difference. The administration of brown sugar with different levels of turmeric in drinking water showed no significant difference (P>0.05) for all the variables measured. However, the application giving is recommended 2% brown sugar and 20 grams of turmeric in drinking water.Key words: Feed intake, Body weight gain, Brown sugar, Curcumin, Broiler